Emergency and clinical ultrasound board review - Chiem, Alan; Dinh, Vi Am (New York, NY : Oxford University Press, 2020)
'Emergency and Clinical Ultrasound Board Review' is a comprehensive guide for preparing for the Advanced Emergency Medicine Ultrasonography or Critical Care Echocardiography board exams, and for residents preparing for in-training examinations in ultrasound. The text consists of over 500 multiple-choice questions, organised into 18 chapters covering ultrasound topics such as physics, eFAST, echocardiography, thoracic, aorta, hepatobiliary, renal, pregnancy, soft tissue, ocular, procedural, airway, ENT, DVT, testicular, abdominal, and musculoskeletal applications. Questions are written in a case-based format that emulates the ABEM and NBE board exams, and are supplemented by over 800 figures, tables, boxes, and online videos.
Also issued in print: 2020.
Specialized.
Description based on online resource; title from home page (viewed on May 28, 2020).
Keywords: Ultrasonic imaging -- Examinations, questions, etc; Emergency medicine -- Examinations, questions, etc